2017
DOI: 10.1111/sji.12580
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5a‐Induced Changes in Neutrophil Morphology During Inflammation

Abstract: The complement and neutrophil defense systems, as major components of innate immunity, are activated during inflammation and infection. For neutrophil migration to the inflamed region, we hypothesized that the complement activation product C5a induces significant changes in cellular morphology before chemotaxis. Exposure of human neutrophils to C5a, dose- and time-dependently resulted in a rapid C5a receptor-1 (C5aR1)-dependent shape-change, indicated by enhanced flow cytometric forward-scatter area values. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 56 publications
11
72
1
1
Order By: Relevance
“…Here, we present a novel observation describing the series of MORE changes that occur in neutrophils following exposure to priming agents and demonstrate an overlap of the morphological and functional properties of neutrophils. It has been reported that polarization and reorganization of the actin cytoskeleton increase with neutrophil migration, facilitating invasion at inflammatory sites and the clearance of pathogens . We speculate that the MORE changes seen in neutrophils may allow for neutrophils to be freed from entrapment within microvasculature .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Here, we present a novel observation describing the series of MORE changes that occur in neutrophils following exposure to priming agents and demonstrate an overlap of the morphological and functional properties of neutrophils. It has been reported that polarization and reorganization of the actin cytoskeleton increase with neutrophil migration, facilitating invasion at inflammatory sites and the clearance of pathogens . We speculate that the MORE changes seen in neutrophils may allow for neutrophils to be freed from entrapment within microvasculature .…”
Section: Discussionmentioning
confidence: 77%
“…In addition to the described functional and biochemical changes, neutrophils undergoing activation exhibit morpho‐rheological (MORE) changes to their biophysical shape. It has been reported that activated neutrophils are smaller and stiffer than their unactivated and un‐primed counterparts, although there exist conflicting reports of neutrophils expanding poststimulation . Travel into and through the microcapillary system is essential for neutrophil migration to sites of infection or damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63] Recent reports by Denk and colleagues demonstrated that C5a-C5aR1 interactions lead to iondependent changes in intracellular pH and fluid content, driving neutrophil degranulation, shape change and chemotaxis. 64,65 C5aR1 ligation also prolongs neutrophil survival through potentiation of the Akt/Bad pathway and decreasing activity of the pro-apoptotic caspase 9. 42,66,67 In neutrophils, the effects of C5a on ROS production and apoptosis have been demonstrated to be dependent on phosphoinositide signalling.…”
Section: C5a Signalling In Cells Of the Immune Systemmentioning
confidence: 99%
“…1C, n=60, 000). Circularity feature is a parameter for evaluating the irregular cell contour in image flow cytometry system [30]. However, some LPS-treated DCs with low miR-590-5p-Cy3 fluorescence intensity had a high level of CD11c (Fig.…”
Section: The Internalization Of Mirna As a Measure Of The Target Of Ementioning
confidence: 99%